Analisis Sistem Pengambilan Keputusan dalam Pembelian Mobil Menggunakan Metode Analytical Hierarchy Process - Dewi Auditya Marizka; Wilda Sukmawati; Irma Agustiningsih; Indra Yusuf; Andi Rusnaenah (NUCLEUS, 2023)
Along with the development of the times the demand for four-wheeled vehicles is increasing, because it is undeniable that four-wheeled vehicles are very much needed by the people to support their daily activities such as in terms of work, vacation, and etc. Certainly in terms of choosing a four-wheeled vehicle it must be adjusted to the individual's needs, because a car with different types or specifications will have different functions as well. There are various kinds of criteria in terms of choosing a car that must be considered by the individual concerned. This is what motivates us to conduct research using the Decision Support System (DSS) in the process of selecting four-wheeled vehicles by implementing the Analytical Hierarchy Process (AHP) method carried out by weighting and setting priorities so that ultimately the best alternative is to choose four-wheeled vehicles.